Does Papillary Carcinoma of Thyroglossal Duct Cyst Develop De Novo?. (16th August 2015) - Baglam, Tekin; Binnetoglu, Adem; Yumusakhuylu, Ali Cemal; Demir, Berat; Askan, Gokce; Sari, Murat
Abstract : Backround . Thyroglossal duct cyst (TDC) is a developmental abnormality of the thyroid gland. Due to embryological remnants of thyroid tissue located in the TDC, the same malignant tumors that develop in the thyroid gland can also develop in the TDC. Methods . We present the unique case of a 39-year-old female with simultaneous de novo papillary carcinoma in a TDC and the thyroid gland. Results . With the suspicion of simultaneous papillary carcinoma in the TDC and the thyroid gland, Sistrunk procedure with total thyroidectomy and central neck exploration was performed. Conclusion . The clinician should have a high index of suspicion upon encountering papillary carcinoma of the TDC to differentiate de novo papillary carcinoma in the TDC from those originating from the thyroid gland, because papillary carcinoma in TDC may originate from an occult thyroid papillary carcinoma.